Spatially activated conserved auxin-transcription factor regulatory module controls de novo root organogenesis in rice - Garg, Tushar; Yadav, Manoj; Mushahary, Khrang Khrang Khunggur; Kumar, Akshay; Pal, Vivek; Singh, Harshita; Jain, Mukesh; Yadav, Shri Ram (Planta, 2023)
This study reveals that the process of crown root development and auxin-induced de novo root organogenesis during in vitro plantlet regeneration share a common auxin-OsWOX10 regulatory module in rice.